Tribological behaviour of a PEEK polymer containing solid MoS2 lubricants. (1st May 2015) - Zalaznik, M.; Novak, S.; Huskić, M.; Kalin, M.
Abstract: The addition of different concentrations (2–10 wt.%) of molybdenum disulfide (MoS2 ) to a poly–ether–ether–ketone matrix has been studied in terms of the thermal, mechanical and tribological properties of the materials. The results of dry‐sliding tribological tests, differential scanning calorimetry and scanning electron microscope–energy‐dispersive X‐ray (EDS) analyses show that the concentration of MoS2 influences the tribological, mechanical and thermal properties. With the highest concentration of MoS2 (10 wt.%), the coefficient of friction was reduced by as much as 25%, while the maximum reduction in the wear rate was ~20%, which required 5 wt.% of MoS2 . The most important parameter when it comes to achieving an improved tribological behaviour was found to be the combination of a high hardness and a sufficient quantity of transfer film being formed. Copyright © 2015 John Wiley & Sons, Ltd.